Pengaruh Current Ratio, Return On Equity, dan Total Asset Turnover Terhadap Earning Per Share (Studi Empiris: Pada Perusahaan Sektor Kertas Dan Pulp Yang Terdaftar Pada Bursa Efek Indonesia Periode Tahun 2013 – 2017) - Wahyu Abadi; Hermansyah Hermansyah (Neraca : Jurnal Akuntansi Terapan, 2019)
The purpose of the research is to examine the influence of Current Ratio, Return On Equity, and Total Asset Turn Over on Earning Per Share. The sample of this research is a paper and pulp companies listed on the Indonesia Stock Exchange period 2013 – 2017 as much as 4 companies in 5 period. Data collected from financial report from year ended 2013 – 2017. This research is used quantitative approach with a type of correlational research. This research using multiple linier regression methods with the SPSS version 24 Programs. The results of the analysis show that as simultaneously, the Current Ratio, Return On Equity, and Total Asset Turn Over have a significant effect on Earning Per Share. It showed by significant value of F-test 0,000 lower than 0,05.